Corporate Education and the Role of the Chief Learning Officer - Hourneaux Junior, Flavio (2008)
This paper aims to present an overview on characteristics, roles and responsibilities of those who are in charge of the Corporate Educational Systems in several organizations from distinct industries in Brazil, based on a research carried out by the authors. The analysis compares what is available in the literature on this subject so that it may provide insights on how Brazilian companies have dealt with the difficult task of developing competences in their employees. Special attention is given to the Chief Learning Officer’s role (or the lack of it) – someone who was supposed to be in charge of the employees’ development processes in a given organization. The results show that this role has not been a clear or unanimous concept yet, neither in terms of the functions to be performed nor the so-called strategic importance given to this sort of executive. This research is both exploratory and descriptive, and due to the use of intentional sample, the inferences are limited. Despite these limitations, its comments may enrich the discussion on this subject.Key-words:Corporate education. Corporate university. Chief learning officer.